Penerapan Restorative Justice Dalam Penyelesaian Perkara Pidana Oleh Lembaga Penegak Hukum Di Indonesia: (Berdasarkan Nota Kesepakatan Bersama Ketua Mahkamah Agung, Menteri Hukum dan Ham, Jaksa Agung dan Kepala Kepolisian Tahun 2012) - Kholidazia El HF.; Muhammad Zainal (JUSTNESS - Jurnal Hukun dan Agama, 2021)
The research on "The Application of Restorative Justice in the Settlement of Criminal Cases by Law Enforcement Agencies in Indonesia (Based on a Memorandum of Understanding with the Chief Justice of the Supreme Court, Minister of Law and Human Rights, Attorney General and Chief of Police in 2012)" aims to: 1) to know and understand decisions about the types of criminal acts that can be applied by Restorative Justice in the Memorandum of Understanding with the Chief Justice of the Supreme Court, the Minister of Law and Human Rights, the Attorney General and the Chief of Police in 2012; 2) to analyze the application of Restorative Justice carried out by Law Enforcement Agencies in Indonesia based on the Memorandum of Understanding with the Chief Justice of the Supreme Court, the Minister of Law and Human Rights, the Attorney General and the Chief of Police in 2012. This research uses normative legal research or library law research or also called literary studies with a statutory approach where it is necessary to understand the hierarchy and principles in statutory regulations. Based on the results of the study, broadly speaking, the results of this study can be concluded as follows:a. Types of Crimes That Can Be Settled Through Restorative Justice 1) The Supreme Court of the Republic of Indonesia in General Courts: Minor crimes, cases of women in conflict with the law, cases of children in conflict with the law and narcotics cases; 2) at the Indonesian Prosecutor's Office: The suspect has committed a crime for the first time, the crime is only threatened with a fine or is threatened with imprisonment of not more than 5 (five) years and the crime is committed with the value of the evidence or the value of the loss caused as a result of the crime. a criminal offense of not more than Rp. 2,500,000 (two million five hundred thousand rupiah); 3) in the Indonesian National Police: all crimes against general crimes that do not cause human victims.b. Application of Restorative Justice 1) in the Supreme Court of the Republic of Indonesia in the General Courts Environment: The application of Restorative Justice is adjusted to the type of criminal case, however, the principle of application is the same, namely by seeking peace and compensation; 2) at the Attorney General's Office of the Republic of Indonesia: by making peace efforts between the suspect and the victim; 3) in the Indonesian National Police: efforts to reconcile and settle disputes between the litigants (the reporting party, and/or the family of the reporting party, the reported party and/or the family of the reported party and representatives of community leaders) with the investigator's superiors knowing. Keyword: Law, Restorative Justice